Epidemiology of sleep-related complaints associated with sleep-disordered breathing in Bangkok, Thailand - Puntarica Suwanprathes (2018)
Background: This study assesses the prevalence of and risk factors for sleep-related complaints in Bangkok, Thailand. Methods: A representative sample of the Bangkok population was selected based on results of the 2000 Census. A total of 4680 participants underwent face-to-face interview with a 49-question sleep inventory. Results: Four percent of the total sampled (5.3% of men and 3.5% of women) complained of habitual snoring (>3 nights/week) and excessive daytime sleepiness (>3days/week) for at least 3months. These subjects were significantly (p<0.0001) older (41.4 vs. 36.7years), had greater BMI (26.0 vs. 22.8kg/m2), neck size (34.7 vs. 32.5cms), and waist circumference (88.0 vs. 78.7cms). They reported significantly shorter nocturnal sleep time, greater frequency of sleep disturbances and awakenings, unrefreshing sleep, choking during sleep, night sweats, nocturia, and bruxism. There was also a greater prevalence of cardiovascular and endocrine diseases. Multivariate analysis showed that male gender; BMI; waist size; and reports of witnessed apneas, unrefreshing sleep and night sweats were significant predictors of snoring and daytime sleepiness. Conclusion: This is the first epidemiologic study investigating sleep-related complaints and associated health morbidities in the Thai population. © 2010 Elsevier B.V.